2005
DOI: 10.1007/s00778-004-0127-3
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative joins in a pervasive computing environment

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…While existing context query languages support only a subset of the features mentioned above, CQL stands out by supporting all of them. This is also supported by the evaluation presented in Haghighi et al, which identified the CML and the RDF‐based MoGATU as the two most sophisticated systems. However, both of them lack either support for heterogeneous representations and incorporation of ontologies or the provisioning of elaborate aggregation and filtering mechanisms.…”
Section: Reference Architecturementioning
confidence: 84%
“…While existing context query languages support only a subset of the features mentioned above, CQL stands out by supporting all of them. This is also supported by the evaluation presented in Haghighi et al, which identified the CML and the RDF‐based MoGATU as the two most sophisticated systems. However, both of them lack either support for heterogeneous representations and incorporation of ontologies or the provisioning of elaborate aggregation and filtering mechanisms.…”
Section: Reference Architecturementioning
confidence: 84%
“…The SOCAM (Service-oriented Context-Aware Middleware) architecture [15,16] describes context queries in OWL that is a RDF-based language and supports complex context queries by combining predicates and Boolean algebra. Although the structure of RDFbased languages is more suitable for context queries, it is not as flexible as SQL and it can result in large amounts of overheads as it requires creation of many classes, subclasses and relationships [17].…”
Section: Rdf-based Query Languagesmentioning
confidence: 99%
“…One of the innovative works in the area of querying context is CQP (Collaborative Query Processing) protocol that has been implemented on top of MoGATU framework [17]. MoGATU is a profile-driven and proactive peer-to-peer semantic data management system for pervasive environments that defines queries in DAML-OIL [18].…”
Section: Rdf-based Query Languagesmentioning
confidence: 99%
See 1 more Smart Citation